Assessment on soil fertility status and growth performance of Planted Dipterocarp Species in Perak, Peninsular Malaysia - Arifin, Abdu; Tanaka, Sota; Shamshuddin, Bin Jusop; Nik Mohamad, Bin Ab Majid; Zahari, Bin Ibrahim; Mohd Effendi, Bin Wasli; Sakurai, Katsutoshi (Asian Network for Scientific Information, 2008)
A study was conducted in the rehabilitation of degraded forestland in the Bukit Kinta Forest Reserve, Perak, Peninsular Malaysia with two main objectives: (1) to assess the growth performance of two indigenous dipterocarp species, Shorea pauciflora (King) and S. macroptera (Dyer) planted under various line planting widths and gap planting openings and (2) to examine soil fertility status and site quality of the study area using two indices; Soil Fertility Index (SFI) and Soil Evaluation Factor (SEF), which are commonly used for estimating soil fertility of secondary forest in humid tropical regions. The survival rate of the two species was not affected by line planting width and gap planting opening. However, its effect on the tree growth was very clear probably due to preference of light intensity under the canopy, which in turn can be controlled by line planting widths and gap planting openings. Principal component analysis categorized the soil properties into three principal components which explained 70% of the total variation. The First Component Score (PC1) was related to cation retention capacity with a high contribution of soil organic matter. The linear regression analysis indicated that there were positive correlations between PC1 score and the proposed SFI and SEF for both soil depths (p < 0.01). The SFI and SEF were also highly correlated with height, dbh (diameter at breast height) and tree volume, while PC1 score was only correlated with dbh and tree volume for the surface soils. This shows that the SFI and SEF can be used as indices to predict soil fertility and site quality of rehabilitated degraded forestland.